Management of Madrasah Tsanawiyah's Marketing Mix Strategy in Increasing New Student Interest - Abdul Fatah; Abdus Salam DZ; Imam Tabroni; Abdul Karim; Jalaludin; Maftuhah Dewi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
In today’s competitive educational landscape, madrasahs must actively engage in marketing strategies to ensure their sustainability and growth. Without effective promotion, even a well-managed institution may face declining student enrollment. This study aims to explore the marketing strategies of Madrasah Tsanawiyah Minhajut Tholabah Purbalingga in order to maintain its existence and attract prospective students. The research employs a descriptive qualitative approach through field studies, with data collected using interviews, observations, and documentation. The data analysis follows three stages: data reduction, data presentation, and conclusion drawing, while the validity of findings is ensured through triangulation techniques. The results reveal that the madrasah adopts a marketing mix strategy based on the 7P framework: product, price, place, promotion, people, physical evidence, and process. Each element is strategically utilized to highlight the uniqueness of the madrasah, strengthen community trust, and build a positive institutional image. The findings indicate that implementing a comprehensive and well-structured marketing mix enhances the competitiveness of Madrasah Tsanawiyah Minhajut Tholabah in attracting new students and sustaining its reputation. The contribution of this study lies in providing practical insights into how Islamic educational institutions can adopt modern marketing principles without compromising their core religious and cultural values. This research not only enriches the discourse on education management but also offers a replicable model for other madrasahs facing similar enrollment challenges. By integrating conventional marketing strategies with the mission of Islamic education, the study demonstrates how madrasahs can achieve both institutional sustainability and community development.